Gut microbiota-brain bile acid axis orchestrates aging-related neuroinflammation and behavior impairment in mice - Junli Ma; Mingxiao Li; Yiyang Bao; Wenjin Huang; Xiaofang He; Ying Hong; Wenjing Wei; Zekun Liu; Xinxin Gao; Yang Yang; Zhengyu Cui; Wantao Wang; et al. (Elsevier, 2024)
Emerging evidence shows that disrupted gut microbiota-bile acid (BA) axis is critically involved in the development of neurodegenerative diseases. However, the alterations in spatial distribution of BAs among different brain regions that command important functions during aging and their exact roles in aging-related neurodegenerative diseases are poorly understood. Here, we analyzed the BA profiles in cerebral cortex, hippocampus, and hypothalamus of young and natural aging mice of both sexes. The results showed that aging altered brain BA profiles sex- and region- dependently, in which TβMCA was consistently elevated in aging mice of both sexes, particularly in the hippocampus and hypothalamus. Furthermore, we found that aging accumulated-TβMCA stimulated microglia inflammation in vitro and shortened the lifespan of C. elegans, as well as behavioral impairment and neuroinflammation in mice. In addition, metagenomic analysis suggested that the accumulation of brain TβMCA during aging was partially attributed to reduction in BSH-carrying bacteria. Finally, rejuvenation of gut microbiota by co-housing aged mice with young mice restored brain BA homeostasis and improved neurological dysfunctions in natural aging mice. In conclusion, our current study highlighted the potential of improving aging-related neuro-impairment by targeting gut microbiota-brain BA axis.